Cost-effectiveness Analysis in Indonesian Primary Education - Maman Suryaman (Language, Literature and Education: Research Updates Vol. 4, 2025)
This article examines the cost-effectiveness of primary education in Indonesia, emphasising critical issues such as requirement assessment, budget policy formulation, efficiency and cost measurement, and performance and target cost evaluation. Cost-effectiveness analysis (CEA) in education evaluates the economic efficiency of educational programs and offers guidance for resource allocation. It evaluates expenditures and results, which are essential for managing constrained budgets and the necessity for heightened accountability in educational financing. Cost-effectiveness in education is essential for optimising benefits relative to expenditures, given that educational systems encounter financial limitations. Various approaches, including cost-benefit analysis, cost-effectiveness analysis, cost-utility analysis, and cost-minimisation analysis, offer intricate insights into educational investments. Comprehending these distinctions is crucial for researchers performing evaluations. Cost-effectiveness analyses empower educators to make informed decisions grounded in both quantitative and qualitative results. Research has found potentially cost-effective ways to implement educational interventions, including peer-led and organised programs for health-related subjects. Furthermore, financial aid programs are essential for enhancing educational accessibility and maximising educational efficacy. Understanding the economics of educational systems, including resource distribution and technological investment, is crucial for optimising educational efficacy. Cost-effectiveness encompasses not just direct cash expenditures but also necessitates a thorough analysis of opportunity costs and prospective returns from educational initiatives. Educational assessments must take into account the wider socio-economic context to evaluate both short-term and enduring effects. This project aims to improve accessibility and educational outcomes for all students.